Rethinking Supply Chain Disruption Strategy to Address Challenges of Diversification and Substitution as an Instrument Contingency in Some Manufacturing Firms in Indonesia - Darwin Raja Unggul Saragih (Jurnal Indonesia Sosial Sains, 2023)
The COVID-19 pandemic disrupted supply chains that had not yet recovered and were again affected by the Russian invasion of Ukraine. This situation threats the global economy with stagflation and significantly impacts some manufacturing firms in Indonesia. The researcher focuses on alternative solution strategies as a direct consequence of the supply chain disruption. This study was conducted on some manufacturing firms currently facing significant problems with raw material supply. The researcher adopts a qualitative review methodology and in-depth interviews with a limited number of n=19 participants to find data analysis. An overview of findings as a basis for subsequent relevances and understanding for manufacturers considering developing relationship-integrated domestic supply chains. The operations of manufacturing firms that depend on imported raw materials must be shut down, resulting in rising prices. It is challenging for manufacturers to raise the price of finished goods. Manufacturers must begin developing domestic supply chains to be more cost-effective and to support sectors amid uncertainty and complexity in demand for future supply.